The effect of anti-oxidant agents as neutralizers of bleaching agents on dentin bond strength - Al-Bayaty, Ayad Mahmoud; Al-Rawi, Inas I (Journal of Baghdad College of Dentistry, 2013)
Background: Reduction in bond strength when bonding was done immediately after intracoronal bleaching procedure has been recognized. The purpose of this study is to assess the effect of antioxidants (10% sodium ascorbate (SA), 0.1M thiourea and7% sodium bicarbonate (SB)) on reversing bonding strength of composite resin to bleached dentin. Materials and method: Sixty upper 1st premolar teeth, were selected, the crowns of the teeth were embedded in acrylic resin blocks exposing a flat dentin from the buccal surface, then divided into 6 groups (10 samples each). Bleaching for the experimental groups was performed using 35% hydrogen peroxide bleaching gel (pola–office).Group A (Negative control group; dentin samples immediately bonded with composite without bleaching)Group B (Positive control group; dentin samples bleached and immediately bonded with composite). Group C (Dentin samples bleached and stored for 14 days in DDW then bonded with composite). Group D (Dentin samples bleached and treated with 10% (SA) then immediately bonded with composite). Group E (Dentin samples bleached and treated with 0.1M thiourea then immediately bonded with composite). Group F (Dentin samples bleached and treated with 7% SB then immediately bonded with composite).The shear bond strength was determine using instron testing machine. Results: Bleaching the dentin with 35 % hydrogen peroxide gel for 24 minutes resulted in reduction in bond strength of the bleached teeth when bonding was performed immediately after bleaching. Delayed bonding of composite to the bleached dentin for 14 days will result in a highly significant increase in the shear bond strength. Conclusion: Treating the bleached dentin with 10% (SA) in water base showed a highly significant increase in the shear bond strength of the composite to dentin and reversing the bond strength value to the level of the unbleached dentin. Treating the bleached dentin with 0.1M thiourea significantly increased the shear bond strength of the composite to dentin.